The effects of deformation-induced microstructures on intragrain Ar(40)/Ar(39) ages in potassium feldspar - Reddy, Steven; Potts, G.; Kelley, S.; Arnaud, N. (Geological Society of America, 1999)
A combination of forescatter scanning electron microscopy and both ultra-violet (UV) laser and cycle stepped-heating 40Ar/39Ar dating techniques have been applied to a single deformed grain of potassium feldspar to investigate the relationship between microstructure and 40Ar/39Ar isotope systematics. The form and distribution of deformation-induced microstructures has been mapped using intragrain variations in lattice orientation. These variations are related to thin section and regional structural data to provide a well-constrained deformation history for the feldspar grain. Thirty laser 40Ar/39Ar analyses show age variations that correlate with the internal microstructure. Stepped-heating data provide further evidence of this relationship. Our approach allows the recognition of different Ar reservoirs within the deformed feldspar and identifies microstructural controls on Ar migration. Such a relationship has important implications for the understanding and interpretation of 40Ar/39Ar geochronological data and the subsequent use of such data to constrain the temperature - time evolution of deformed rocks.